Quantitative assessment of progressive laryngeal hemiplegia in a 4‐year‐old beagle. Issue 1 (26th November 2021) - Martin‐Flores, Manuel; Sakai, Daniel M.; Cheetham, Jonathan
Abstract: Progression of unilateral laryngeal paralysis (LP) was quantified in an asymptomatic 4‐year‐old beagle during spontaneous breathing stimulated with inhaled 10% CO2 . Laryngeal evaluation was performed sequentially to track progression of LP over an 18‐month period. Videos of the larynx during CO2 ‐stimulated breathing were obtained under propofol anaesthesia. Maximal inspiratory normalised glottal gap area (NGGA) was determined on each occasion for left and right hemiglottis. Left NGGA was smaller than the right side throughout the period of follow‐up. After 18 months, LP had progressed to such a degree that the left arytenoid was completely paralysed with no movement during inspiration. This case report demonstrates the possibility of early detection of LP, and quantification of progression. Early detection may allow regenerative surgical strategies for LP to maintain glottic area and reduce postoperative complication rates.